Efesiensi Pengawasan Atas Penegakan Peraturan Daerah Kabupaten Badung Nomor 3 Tahun 1992 Tentang Jalur Hijau - I Wayan Winarsa (Universitas Mahendradatta Denpasar, 2020)
This research is motivated by the fact that this Regional Regulation and at the time between the Badung Regency and the City of Denpasar were still one, but this regulation was still used by the Badung Regency Government. The purpose of this study was to find out how much this local regulation was applied in the Badung Regency. The results of the study show that there is a need for new regulations in the context of monitoring the enforcement of the Badung regency regulation in lieu of regulation No. 3 of 1992 concerning green lanes, due to the rapid utilization of green lanes as residential areas.